PENETAPAN KADAR FLAVONOID EKSTRAK DAUN KELAKAI (Stenochlaena palustris (Burm. F.) Bedd.) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Syamsul, Eka Siswanto; Hakim, Yana Yunita; Nurhasnawati, Henny (Jurnal Riset Kefarmasian Indonesia, 2019)
Kelakai (Stenochlaena palustris (Burm F.) Bedd.) is a medicinal plant of Borneo. The purpose of this research is to determine the level of flavonoid in crude extract of kelakai leaf by UV-Vis Spectrophotometer. The research was conducted by collection of the kelakai leaves and plant determination. The ethanolic extract of kelakai leaves was collected using macceration methode. The determination of flavonoid level was conducted by UV-Vis Spectrophotometer using quersetin as standard compound. The study showed that the rendemen of crude extract of kelakai leaf was (22,92%). The moisture content in viscous extract was (19,71%). The level of Flavonoids in extract was (2,2159±0,083%).